Social relationships and identity online and offline: a study of the interplay between offline social relationships and facebook usage by Rhodes University students from socially disadvantaged backgrounds - Chatora, Arther Tichaona (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
Based on in-depth focus group and individual interviews, this thesis examines how Rhodes University students from socially disadvantaged backgrounds experience campus social life and how they subsequently use Facebook to perform, represent and negotiate their social identities. The study discusses utopian and dystopian positions and interrogates these theoretical perspectives in relation to the students"Ÿ Facebook usage. The popularity and uptake of Facebook by students from disadvantaged backgrounds, such as those here at Rhodes University, is a growing phenomenon, provoking questions about the relationship between social experiences, social identity and social networks. Rhodes University"Ÿs social space has been identified by previous studies as modern, liberal, "elite" and divided along race and class lines. The ways in which students experience this campus social space relates to their subject positions and identities. The study employs different perspectives of identity construction to interrogate the students"Ÿ subject experiences in home and school contexts before coming to Rhodes University. The students"Ÿ subjective positions are primarily embedded in tradition and their subject positions are sometimes in tension or come in conflict with the modern and liberal elements permitted by the Rhodes University context. The students also experience and adopt modern and liberal elements in their lifestyles which are permitted within the Rhodes University social space. The thesis found that Facebook offers a platform which facilitates a social connectivity that influences how students perform their identities in relation to their offline social identities and lived social experiences. This study concludes that the mediated symbolic materials for the construction and negotiation of identity provided by Facebook are sometimes in tension with the demands of traditional subjectivities experienced by these students at Rhodes University. Facebook allows the students to reinforce and affirm the validity of their traditional identities in this modern and liberal space. However, it also emerged that Facebook facilitates and allows students who experience and incorporate the modern and liberal elements permitted at Rhodes University to represent and negotiate their subjective positions online. The findings of the study indicate that participants primarily communicate with their friends, families, relatives and acquaintances - people they know personally offline, in line with the theoretical position which argues that online relationships are primarily shaped by offline relationships.
Keywords: Facebook (Electronic resource); Online social networks; Information technology -- Social aspects; Identity (Psychology) and mass media; Rhodes University -- Students -- Social life and customs; Rhodes University -- Students -- Social networks; Rhodes University -- Students -- Social conditions